SOCIO-DEMOGRAPHIC FACTORS, ACCESS TO THE MASS MEDIA AND THE AGE OF FIRST SEXUAL INTERCOURSE ON YOUNG WOMEN IN INDONESIA (ANALYSIS OF IDHS 2012) - Nurul Fadilah; Andrei Ramani; Ni'mal Baroya; Iswari Hariastuti (Jurnal Kesehatan Masyarakat Andalas, 2018)
Premarital sex is one of young women high-risk reproductive health problem in Indonesia. These problems followed by negative impacts such as unwanted pregnancy, sexually transmitted diseases, and HIV/AIDS. The purpose of this study is to analyze the relationship of socio-demographic factors, mass media access, and the first age of sexual intercourse in young women in Indonesia. Analytic research with cross sectional design was used in this research using secondary data of Indonesia Demographic Health Survey (IDHS) in 2012. Sample size of this research are 8,902 unmarried young women aged 15-24 years, which excluded consecutively to 8,780 samples. Data analysis techniques using chi square and logistic regression with 5% significance level. The results indicated young women who had premarital sex as much as 1,8%, major social-demographic factors with the first age of sexual intercourse are: age, education, family economic status, and employment status. Mass media access significant factor to the first age of sexual intercourse, such as variety access of mass media, type of mass media, and the mass media access intensity. Improvement of PIK-R services is required in giving information about maturing marital age, UPKS program improvement, and role of peer-counselors and peer educators in young women reproductive health.Â Keywords: sexual intercourse, young women, IDHS 2012